2004
DOI: 10.1117/12.511801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric turbulence on imaging quality of electro-optical sensors in different climates

Abstract: During long-term experiments FGAN-FOM measured Cn2 values over land with identical scintillometers in two different climates, in moderate climate in mid-Europe and in arid climate. Since Cn2 usually changes as a function of time-of-day and of season its influence on electro-optical systems can only be expressed in a statistical way. The cumulative frequencies of occurrence were calculated for a time period of one month for different times of the day. The statistical analysis was applied to calculate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As an example for very different meteorological conditions one winter month, January (left hand graph) and one summer month, July (right hand graph) were selected. The diurnal runs of C n 2 differ significantly from the ones derived from our measurements over land in arid climate (Negev, Israel) and moderate climate (Germany, Central Europe), for details see 8,9 . Over sea, in summer the characteristic maximum at midday can hardly be observed in general.…”
Section: Analysis Of C N 2 Measurements Over Seamentioning
confidence: 92%
“…As an example for very different meteorological conditions one winter month, January (left hand graph) and one summer month, July (right hand graph) were selected. The diurnal runs of C n 2 differ significantly from the ones derived from our measurements over land in arid climate (Negev, Israel) and moderate climate (Germany, Central Europe), for details see 8,9 . Over sea, in summer the characteristic maximum at midday can hardly be observed in general.…”
Section: Analysis Of C N 2 Measurements Over Seamentioning
confidence: 92%
“…For other parametric value adequate models, e.g. described as strong turbulence models [8] or reference measurements in from other climates [16], are to be applied. Not all possible cases (e.g.…”
Section: Figure 4: Visualization Of the Theoretic Models In Image Unimentioning
confidence: 99%
“…In addition, studies have shown that active laser imaging systems can obtain images of non-line-of-sight targets hidden around corners 8 . The imaging quality is mainly affected by the backscattering 9 , attenuation and turbulence caused by the scattering medium 10 . Meanwhile, more backscattered radiation can be eliminated by adjusting the laser pulse frequency and shutter 11 .…”
Section: Introductionmentioning
confidence: 99%